Penyuluhan Dampak Perjudian Online dan Penyalahgunaan Narkoba Pada Perekonomian Masyarakat Dikalangan Desa Beratkulon Kecamatan Kemlagi - Ghozali Ghozali; Sintya Meirna Eka Putri; Achmad Risdiyanto; Habil Abdillah; Fatmawati Fatmawati; Delfia Resti Amalia; Nafis Syafaatul Awaliyah; Selvia Marcelina; Gigih Ardiansyah Suwarsono; Satria Zanu Kurniawan; Lailul Muqaromah; Amzaq Bagus Purnomo; Muhammad Hanif Fandi; Wahyu Linggar Pamuji; Abi Wahyu Rosabi; Widia Herdianti; Chandra Ayu Pancalara Sakti; Nida’ Nur Anisah; Cucu Irma Firnanda; Ananda Mar’atus Sholikhah; Al Fina Kusuma Putri; Bayu Permana Putra; Ferdinan Yohanes; Shultan Alif Firmansyah (Jurnal Pengabdian Kepada Masyarakat, 2025)
This study aims to analyze the impact of online gambling and drug abuse on the economy of the community in Beratkulon Village, Kemlagi District. The method used in this research involves socialization and discussions with local residents to gather data and information regarding the issues faced. The results indicate that online gambling and drug abuse not only lead to financial losses for individuals but also trigger family conflicts, accumulation of debt, and loss of community productivity. Furthermore, the lack of education about the dangers of drugs and weak supervision are contributing factors to the increasing cases of abuse. This research recommends the need for enhanced community awareness through more intensive educational and socialization programs, as well as strengthening the role of media in disseminating positive messages to prevent drug.